Efektivitas Metode Menghafal Al-Qur’an Di Pondok Pesantren Tahfidzul Qur’an Al-Asy’ariyyah Kalibeber Wonosobo (Studi Perbandingan Menggunakan Al-Qur’an Terjemah Dan Non Terjemah) - Khoirul Madzkuroh; Ngarifin Shidiq; Ahmad Robihan (Sevaka : Hasil Kegiatan Layanan Masyarakat, 2025)
This research aims to: 1) to know the condition of students in memorizing the Qur'an using translated and non translated Al-Qur'an at PPTQ Al-Asy'ariyyah Kalibeber Wonosobo; 2) to know the effectiveness of the method of memorizing translated and non translated Al-Qur'an at PPTQ Al-Asy'ariyyah Kalibeber Wonosobo; 3) to know the factors that influence the effectiveness of the method of memorizing Al-Qur'an using translated and non translated Al-Qur'an at PPTQ Al-Asy'ariyyah Kalibeber Wonosobo. This thesis uses a comparative descriptive qualitative research approach. Where researchers understand phenomena or events through an in-depth description of the data collected in the form of words not numbers. And comparing in depth (qualitative) about a phenomenon, with the aim of identifying similarities and differences, as well as understanding the context and meaning behind it. The data collection technique uses observation, interviews, and documentation. The data analysis techniques used in comparative descriptive qualitative analysis are data selection, data classification, data interpretation and the final step of comparison, where researchers compare the speed level of memorizing the Qur'an with the use of different Qur'ans but using the same method. The results showed that: 1) the condition of students who memorize using the translated Al-Qur'an tends to have a better understanding of the meaning of the verse, but the memorization process is slower because it takes time to understand the meaning of the verse. Students who memorize using the non-translated Al-Qur'an are faster in memorizing because they only focus on the lafadz and the rhythm of the reading. 2) the effectiveness of memorization methods using translated and non-translated Al-Qur'an at PPTQ Al-Asy'ariyyah. In terms of speed, memorizing using the non-translated Al-Qur'an is superior because students only focus on repeating the lafadz. The durability of memorization in both methods is strongly influenced by the consistency of murojaah. Understanding the meaning is better owned by students who memorize using the translated Al-Qur'an. 3) factors that influence the effectiveness of memorization, namely motivation, intelligence, psychological conditions, support from parents and ustadzah, learning environment, as well as time management and discipline are very influential on the success and effectiveness of students' memorization.